MEDICAL WASTE ANALYSIS IN PUBLIC HEALTH CENTER - Anita Dewi Moelyaningrum (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2010)
Public Health Center is one of the institution which produce medical waste. Medical waste must heve good management system because it can effect in public health. The purpose of this research is to evaluate the existing medical waste condition at this Public Health Center, and to evaluate the medical waste system management. That is needed to design a good medical waste management system. The type of research is descriptive research, which used primary and secondary data. Results of this study showed that the main medical waste source was emergency unit (UGD) with a generation rate of 76,06 gr/ day; where as smallest waste source was planning family unit and laboratorium unit with a generation rate of 12,5 gr/ day. The medical waste management system was not properly implemented. Medical waste management system based on the characteristic must be implementated to keep the public health.